The Role of the Constitutional Court in Addressing Centralization Allegations: A Syariah Economic Perspective on Baznas' Contribution to Indonesia's Unified Economic System - Yudi Permana; Ade Sofyan Mulazid; Athia Nur Kamilah; Yoghi Citra Pratama; Muhammad Iman Kurniawan; Miftah Hur Rahman Zh; Supriyono Supriyono (Yayasan Keluarga Guru Mandiri, 2025)
This study provides a comprehensive analysis of the Constitutional Court's role in institutionalizing a centralized governance model for the National Board of Zakat (BAZNAS) and its systemic implications for Indonesia's economic framework from a Shariah economics perspective. By synthesizing extant literature, it elucidates the legal, operational, and philosophical dynamics underpinning BAZNAS’s evolving mandate. Conducted as a Systematic Literature Review (SLR) in accordance with the PRISMA protocol, systematic searches across Scopus and the Watase Uake System identified 95 articles for in-depth thematic analysis. The findings reveal that the centralization of BAZNAS, legitimized by the Constitutional Court’s ruling, establishes a fundamental tension between national administrative efficiency and local philanthropic autonomy. The analysis confirms BAZNAS’s strategic role not only in zakat distribution but also in advancing national objectives of sustainable development and financial inclusion. However, significant governance challenges, particularly regarding transparency and accountability, persistently surface. The research makes a threefold contribution: First, it identifies a critical methodological gap, demonstrating that dominant quantitative approaches have insufficiently captured the qualitative and contextual dynamics behind operational shortcomings. Second, it surfaces underexplored thematic frontiers, notably those of digitalization, technological integration, and BAZNAS’s potential role in global challenges such as climate change. Third, it proposes a structured agenda for future inquiry and practice. The conclusions emphasize the necessity for methodological diversification, comparative international analysis, and deeper investigation into the distributive impacts of centralization and the transformative potential of technology. Practical implications focus on strengthening governance through mechanisms such as blockchain, fostering inter-institutional collaboration, and advocating for more integrative zakat-sector policies. Future research should prioritize rigorous qualitative studies, comparative models, and examinations of BAZNAS’s role in emerging areas such as green finance and the digitalization of Islamic social finance.